Pupil size variation as an indication of affective processing - Partala, Timo; Surakka, Veikko (International journal of human-computer studies, 2003)
The present objective was to investigate pupil size variation during and after auditory emotional stimulation. Thirty subjects’ (15 females and 15 males) pupil responses were measured while listening to 10 negative and 10 positive highly arousing sounds (e.g. a baby crying and laughing), and 10 emotionally neutral sounds (e.g. regular office noise). The subjects also rated their subjective experiences related to the stimuli. The results showed that the pupil size was significantly larger during both emotionally negative and positive stimuli than during neutral stimuli. The results for the time period of 2 s following the stimulus offset showed that pupil size was significantly larger after both negative and positive than neutral stimulation. These results suggest that the autonomic nervous system is sensitive to highly arousing emotional stimulation. The subjective ratings confirmed that the stimuli influenced the subjects’ emotional experiences as expected. Further analyses showed that female subjects had significantly larger pupil responses than males only to neutral stimuli and only during the auditory stimulation. In sum, our results showed that systematically chosen stimuli significantly affected the subjects’ physiological reactions and subjective experiences. It could be possible to use pupil size variation as a computer input signal, for example, in affective computing. Auditory emotion-related cues could also be utilized to modulate the user's emotional reactions.